2020
DOI: 10.1212/nxi.0000000000000864
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-wide examination of comorbidity burden and multiple sclerosis disease severity

Abstract: ObjectiveWe assessed the comorbidity burden associated with multiple sclerosis (MS) severity by performing a phenome-wide association study (PheWAS).MethodsWe conducted a PheWAS in 2 independent cohorts: a discovery (Boston, United States; 1993–2014) and extension cohort (British Columbia, Canada; 1991–2008). We included adults with MS, ≥1 Expanded Disability Status Scale (EDSS) score, and ≥1 International Classification of Diseases (ICD) code other than MS. We calculated the Multiple Sclerosis Severity Score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…We obtained the EHR data for eligible participants from the Mass General Brigham (MGB; formerly the Partners) HealthCare system during the same period. 25 , 26 Mass General Brigham began recording electronic prescriptions in 2005. We compared dimethyl fumarate vs fingolimod for the standard-efficacy DMT comparison and natalizumab vs rituximab for the higher-efficacy DMT comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained the EHR data for eligible participants from the Mass General Brigham (MGB; formerly the Partners) HealthCare system during the same period. 25 , 26 Mass General Brigham began recording electronic prescriptions in 2005. We compared dimethyl fumarate vs fingolimod for the standard-efficacy DMT comparison and natalizumab vs rituximab for the higher-efficacy DMT comparison.…”
Section: Methodsmentioning
confidence: 99%
“… 21 , 22 With advances in analytical capability, 23 , 24 electronic health record (EHR) data provide unique features to complement registries. Our group previously integrated registry data from a well-characterized, longitudinal clinic-based cohort with EHR data for developing models to classify MS diagnosis and severity, 25 assessing comorbidity burden, 26 examining long-term disease activity trends, 27 and predicting future relapse. 28 Here, we compared 2 DMT pairs using registry-annotated MS relapse as the outcome and high-dimensional EHR features and doubly robust (DR) estimation strategies to extensively correct for confounding biases.…”
Section: Introductionmentioning
confidence: 99%
“…We previously integrated research registry data from a well-characterized, longterm, clinic-based cohort 19,20 with EHR data for developing EHR-based models of MS classification and neurological disability. 15,21 Here, we leveraged clinical and associated EHR data to develop and test a clinically deployable model for predicting 1-year relapse risk in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing analytical capability 17,18 has enabled the use of electronic health records (EHR) data to facilitate clinical discovery by providing complementary features otherwise unavailable from traditional research registries. We previously integrated research registry data from a well‐characterized, long‐term, clinic‐based cohort 19,20 with EHR data for developing EHR‐based models of MS classification and neurological disability 15,21 . Here, we leveraged clinical and associated EHR data to develop and test a clinically deployable model for predicting 1‐year relapse risk in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The full picture, however, is more complex. Several human phenome-wide association studies identified causal genetic loci that are shared between metabolic and neurological phenotypes [2][3][4][5][6][7][8], suggesting some degree of pleiotropy-a phenomenon whereby one gene variant affects multiple traits.…”
Section: Introductionmentioning
confidence: 99%